Foundation Program Students' Writing: Issues, Contributing Factors, and Suggestions - Guliyeva, Aytaj; Korogluyeva, Fatima; Akhundova, Leyla; Ibrahimzada, Maleyka (ADA University, 2023)
Students encounter several issues in writing related to grammar, vocabulary, developing and organising ideas. Identifying their problems may accelerate the learning of students. However, there is no research in Azerbaijani context. Therefore, this qualitative study aimed to investigate Foundation year students' writing by exploring issues concerning them, factors contributing to the issues arising, and suggestions that may improve learning and teaching of writing. The sample consisted of eighteen participants: nine foundation-year students and nine instructors teaching writing in the Foundation program. Data from instructors was collected through semi- structured interviews, while students participated in focus group interviews. Although all semi- structured interviews were in-person, one of the two focus-group interviews was held online. The findings of this study overlapped with reviewed literature. The majority of issues included lack of ideas, organisation, vocabulary and grammar, and time management; results indicated that school education or unsatisfactory background, lack of reading and motivation, and poor time management were contributing factors, according to interviewees’ responses. The study revealed that frequent feedback, intensive reading tasks and instructor encouragement may have positively impacted foundation students' writing. Based on the findings we developed a workshop plan to address the retake students’ challenges by providing them with techniques for brainstorming ideas and providing peer feedback.
Keywords: English language -- Composition and exercises -- Study and teaching; Academic writing -- Study and teaching (Higher); Language arts -- Student difficulties -- Azerbaijan; Education